Real food heals : eat to feel younger + stronger every day - Mullen, Seamus; Ko, Genevieve (Avery, an imprint of Penguin Random House, 2017)
"Healthy cooking reinvented by top chef Seamus Mullen, with over 125 Paleo-inspired recipes designed to revitalize your health every day. In the high-end food world, "healthy cooking" has long been taboo. But as one of the only high-profile chefs today guided by the understanding that the food we eat has a deep impact on our health, Seamus Mullen has rewritten the old rule that healthy can't be delicious. Seamus's powerful transformation came out of his own health crisis--after a near-death experience brought on by autoimmune disease he'd struggled with for years, he radically changed the way he cooked, both at his restaurants and at home. As a result, the biomarkers of disease disappeared and the constant trips to the ER he experienced while he was sick have come to an end. But what Seamus has been surprised to discover is that this new way of eating--dishes starring real, whole foods such as vegetables and fruits, meats used as garnishes, whole grains, fermented foods, and no refined sugar or gluten--has not only controlled his disease but has also made his body feel younger, stronger, and more energized every day. It is his mission to share his brand of cooking with readers everywhere to inspire them to shift their diets and truly redefine what "healthy eating" can and should be. A powerful manifesto with Seamus's moving journey at its heart, Real Food Heals is packed with 125 easy-to-prepare, Paleo-inspired, and nourishing recipes packed with delicious whole food ingredients, including Kefir Scrambled Eggs with Grated Garlic; Nori Rolls with Olive Oil, Tuna, Avocado, and Sprouts; and Fig Almond Cacao Nib bars. Complete with a 21-day jump-start meal plan, this unique cookbook will help everyone prepare healthy, irresistible food with big flavors every day and put them on the path to total wellness"--